Optimal probabilistic framework for integration of high penetration of distributed energy resources in electrical distribution systems operation - Cordero Bautista, Luis Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Worldwide clean energy policies are accelerating the deployment of distributed energy resources (DERs) integration into the distribution networks aiming to zero-emission targets, system support benefits and cost-effective grid services. Although clean DERs brings opportunities to customers and utilities, they can be unpredictable due to their stochastic nature leading to an increase of the probability of thermal overloading, overvoltage and reverse power flow. Therefore, traditional distribution network operation becomes more complex due to the increasing in variability and uncertainty of high penetration of DERs. It becomes imperative then take into account its stochastic nature to optimize the use and potential value of the DERs to provide crucial statistical information and evaluate their impacts without compromising the grid operation. In this pathway, this thesis explores and develops a novel optimal probabilistic framework to cater for the uncertainties of PV generation, aggregated demand and EVs with the goal to probabilistically maximize PV generation while evaluating and reducing the probability of technical challenges such as overvoltage using confidence interval constraint. Different probabilistic techniques are implemented through this thesis such as the Monte Carlo simulation, the Point Estimate Method, the Cumulant method with probability distribution reconstruction techniques of the Central Limit Theorem and Edgeworth expansion whose statistical information is employed within the optimization process. The efficiency and accuracy of the Cumulant method with Central Limit Theorem and Edgeworth expansion, 2m+1 PEM with Central Limit Theorem and Edgeworth expansion are presented with a detailed comparison in their performances with the Monte Carlo simulation. The validation of the proposed model is carried out using the IEEE 33 bus system, IEEE 69 bus system and a real electrical distribution system 202 bus system with high penetration of PV generation and EVs. Moreover, the application of the novel optimal probabilistic framework is tested in each test system to probabilistically maximize PV generation while effectively reducing overvoltage probability. The proposed method yielded satisfactory results to probabilistically maximize PV generation in terms of higher fitting accuracy of statistical information and optimal probability distribution for voltage, current, power flow through lines, PV generation with an efficient computational processing with promising application to industries.

As políticas energéticas mundiais estão acelerando a integração dos recursos energéticos distribuídos (REDs) nas redes de distribuição visando metas de zero emissões de carbono, suporte e serviços na operação da rede de maneira accessível e econômica. Embora os REDs tragam oportunidades para clientes e concessionárias, sua natureza estocástica aumenta a probabilidade de sobretensão, sobrecarga, e fluxo reverso de potência. Portanto, a operação ótima da rede de distribuição com a alta penetração dos REDs torna-se mais complexa. Por esse motivo torna-se imperativo ter em conta a natureza estocástica dos REDs para otimizar o uso e o potencial dos REDs, assim como também utilizar as informações estatísticas para avaliar seus impactos sem comprometer a operação da rede. Nesse contexto, esta tese explora e desenvolve uma nova abordagem ótima probabilística para atender às incertezas da geração fotovoltaica (FV), demanda agregada e carregamento de veículos elétricos (VEs) com o objetivo de probabilisticamente maximizar a geração FV enquanto se reduz a probabilidade da sobretensão usando uma restrição de intervalo de confiança. Diferentes técnicas probabilísticas são implementadas ao longo desta tese, como o método de Simulação de Monte Carlo, o Método de Estimação de Pontos, o Método dos Cumulantes, e técnicas de reconstrução da distribuição de probabilidade como o Teorema do Limite Central e a expansão de Edgeworth, são empregadas na análise probabilística cujas informações são usadas no processo de otimização. A eficiência e precisão dos métodos probabilísticos com as curvas aproximadas de probabilidade são comparadas e avaliadas nos sistemas de IEEE 33 barras, IEEE 69 barras e um sistema elétrico de distribuição real 202 barras com alta geração FV e carregamento de VEs para maximizar a geração FV. Além disso, a aplicação do algoritmo ótimo probabilístico é avaliada em cada sistema teste com o intuito de probabilisticamente maximizar a geração FV enquanto se reduz efetivamente a probabilidade de sobretensão. O método proposto apresentou resultados satisfatórios na optimização probabilística da geração FV, precisão das informações estatísticas e distribuição de probabilidade ótima para tensão, corrente, fluxo de potência nas linhas e geração FV, sob um tempo computacional eficiente com potencial de aplicação na indústria.
Estrutura Probabilística Ótima na Integração de Alta Penetração de Recursos Energéticos Distribuídos na Operação de Sistemas Elétricos de Distribuição
Keywords: Central limit theorem; Cumulant method; Electric vehicle; Edgeworth expansion; Overvoltage probability constraint; Point estimate method; Probabilistic maximization of PV generation; Probabilistic power flow; Probabilistic optimization framework; Algoritmo ótimo probabilístico; Expansão de Edgeworth; Fluxo de potência probabilístico; Método dos cumulantes; Método de estimação de pontos; Otimização probabilística da geração fotovoltaica; Restrição de probabilidade de sobretensão; Teorema do limite central; Veículos elétricos